OP0164-HPR Impact of a nurse-led program of patient self-assessment and self-management axial spondyloarthritis: results of a prospective, multicentre, randomised, controlled trial (COMEDSPA). (12th June 2018) - Moltó, A.; Etchieto, A.; Poiraudeau, S.; Gossec, L.; Claudepierre, P.; Soubrier, M.; Fayet, F.; Wendllng, D.; Gaudin, P.; Dernis, E.; Guis, S.; Pouplin, S.; et al.
Abstract : Background: Nurses should promote self-assessment and self-management skills in order that patients might achieve a greater self efficacy and improvement in patients with axSpA. Objectives: To evaluate the impact of a nurse-led program of self-management/-assessment for disease activity program in axSpA. Methods: Prospective, randomised, controlled, open, 12 month trial (NCT02374749 ). Participants 1/Patients: consecutive Axial SpA patients (according to rheumatologist) attending a clinic of the participating centres were invited 0.2/Nurses :all participated at a 1 day meeting prior the start of the study. Study treatment: a program including: 1) Self-management=a) a video explaining the disease, the interest of smoking cessation in axial SpA, the role of NSAIDs as cornerstone treatment in axSpA in the absence of contra-indications, the interest of physical activity and exercise, followed by a discussion with the nurse; b) physical examination by the nurse to check for the presence of spinal deformitiesand depending on the absence/presence of such deformities projection of a specific video of home-based exercises. 2) Self-assessment: Video presentation of the rationale of the use of a composite index (ASDAS/BASDAI), followed by discussion with the nurse. Explanation by the nurse of the collection, calculation of BASDAI and ASDAS Treatment allocation: after written informed consent, the treatment was allocated randomly via en electronic system. Outcome variables: Primary: The level of coping (0–10, where 0=very well) after 12 months. Other variables: Successful smoking cessation, NSAID intake, Number of home-based or supervised exercise, international physical activity questionnaire (IPAQ). Results: Baseline characteristics of the 502 recruited patients (250 and 252 in the active and control groups, respectively): Age: 46.7±12.2 years, male gender: 62.7%, disease duration: 13.7±11.0 y, Xray sacroiliitis 62.8%, MRI sacroiliitis 65.7%, current biologic treatment: 78.3%, ASDAS-CRP: 1.9±0.8, BASFI: 25.6±22.3. After 1 year, coping levels were lower in the active group, but not significant (2.8±2.0 vs 3.0±2.1, p=0.3). However, there was a significant decrease in the BASDAI in the active group (- 1.2±15.8 vs+1.4±15.7, p=0.03), a significant increase in the number (6.1±28.8 vs −0.4±26.9, p=0.03) and duration (4.3±20.1 vs −1.7±20.7, p<0.01) of the home-exercises in the active group, and a greater IPAQ score in the active group at the end of follow-up (138.4±227 vs 95.6±173, p=0.02). Conclusions: This study highly suggests a short-term benefit of a nurse led program on the self-management and self-assessment for disease activity in a young axSpA population in particular with regard to the frequency and the duration of home exercises. Acknowledgements: This study was conducted thanks to a grant from the French National Research Program (PHRC) thanks to an unrestricted grant from ABBVIE. Disclosure of Interest: None declared